The Influence of Organizational Commitment, Job Satisfaction and Career Development on Employee Performance - Chalil, Nurlisa Rafiqah; Santosa, Awan (Research Horizon, 2024)
This research aims to analyze the influence of organizational commitment, job satisfaction, and career development on the performance of employees of the secretariat of the D.I. Yogyakarta regional people's representative council. The population in this study were employees of the secretariat of the D.I Yogyakarta regional people's representative council with a research sample of 70 respondents. The data collection technique used is primary data with the research instrument used is a questionnaire. The instrument test results stated that the data in the research were proven to be valid and reliable. The classical assumption test states that the data in this study is normally distributed and produces a regression model that is free from multicollinearity and heteroscedasticity. The instrument test results stated that all items in the questionnaire were proven to be valid and reliable. The research results prove that organizational commitment has a significant effect on employee performance. Job satisfaction has a significant effect on employee performance. Career development has a significant effect on employee performance.